Virtual Reality (VR) Potential for Education in the Future: A Bibliometric Analysis - Nasrullah A; Noni, Nurdin; Basri, Muhammad; Humaera, Isna (International Journal of Integrative Sciences, 2024)
Language learning apps, interactive multimedia, and virtual classrooms help students learn independently and differently, improving teaching and achievement. VR brings new scenarios and experiences to education. Many consider it a valuable learning tool. VR education can replace multimedia because it's affordable and improves critical thinking and community engagement. Education VR technology was bibliometrically analyzed from 2020 to 2024 using R Studio and Biblioshyni. VR education articles rose from 34 in 2020 to 172 in 2022. Educational and Information Technology published most VR articles, then Heliyon Journal. USAISR, FT Sam Houston, Wang Y, and Texas, USA are the top ten VR education authors. FT Sam Houston, USA, USAISR, and Texas had the most documents. The US had the most VR education articles from 2020 to 2024. China has 182 articles, Canada 84. Australia, Brazil, Germany, India, South Africa, Spain, and the Netherlands produced 80 articles. Human was the most-used VR term in education from 2020 to 2024, appearing 179 times. COVID-19 shows that time and space shouldn't limit research. VR was most cited in 44 education and IT articles. Chinese authors dominate VR research and US scientific publications, making VR media in education appealing in Indonesia